An extensive review on the consequences of chemical pesticides on human health and environment. (10th February 2021) - Rani, Lata; Thapa, Komal; Kanojia, Neha; Sharma, Neelam; Singh, Sukhbir; Grewal, Ajmer Singh; Srivastav, Arun Lal; Kaushal, Jyotsna
Abstract: Pesticides are contributing in current agriculture to fulfil the need of raising population. Uses of pesticides are not limited to agriculture, but they are also used to control over domestic pests, disease insect vectors and home gardening. But they are very toxic in nature and pose acute risks on the human health and the environment. They negatively affected the agricultural workers and trigger social conflicts when employed extensively and without safety measures. Further, they also have adverse effects on the neighboring communities. Chiefly, agriculture workers meet with both direct and indirect exposure with these chemicals. Common man comes in contact with these chemicals by skin contacting which is due to leaking and drifting of pesticides during mixing and causing serious threat to human health such as diabetes, reproductive disorders, neurological dysfunction, cancer and respiratory disorders. In this review, we discussed classification, mechanisms, benefits and adverse effects of the pesticides on both human beings and the environment. We had also discussed some remedial measures to mitigate their toxicity. In future, research is needed to develop innovative ideas in current farming which are able to decrease the application of chemical pesticides. Graphical abstract: Image 1 Highlights: Types and applications of pesticides. Mechanism of action of pesticides. Impact of pesticides on the environment. Disorders caused due to pesticides. Detection and preventing measures for pesticides.